Avaliação dos aspectos sensoriais, físico-químicos e minerais do suco de uva da variedade benitaka(Vitis vinìfera L.) - Pinheiro, Érika Sousa (2008)
The Brazilian market of table grapes is one of the markets fruit and vegetable that more it grew at the country. The grape is one of the fruits that presents considerable value nutritional, being rich in minerals, vitamins and phenolic compounds, it is also considered an energy food, in reason of the presence of sugars. There is an increase tendency in the production and in the consumption of due grape juice the several ones cultivate obtained and, also, due to the consumer's concern with the health. This work had as objective evaluates the stability of the grape juice obtained by the extraction process through vapor with relationships to the aspects chemical, physic-chemical and sensory, during a period of 210 days of storage at ambient temperature. We performed analyses of water activity, dry residue (%), pH, titrable acidity, soluble solids, color, total phenolics, total anthocyanins, sugars (reducers and total), minerals (K, Na, Ca, Cu, Mg, Mn, Fe and Zn) and sensory tests of acceptance of the grape juice. The results for water activity, dry residue, pH, total phenolics and total anthocyanins showed significant difference with the time of storage (p ≤ 0,05). With relationship to the analysis of minerals, the same ones came stable during the studied period. For the sensory attributes evaluated, only the acceptance of the color and appearance did not vary significantly with the time. The flavor, general impression, intensity of sweetness and natural flavor of grape, besides the purchase intention, they presented significant difference (p > 0,05).